1999
DOI: 10.1038/sj.gt.3300934
|View full text |Cite
|
Sign up to set email alerts
|

Induction of complement attack on human cells by Gal(alpha1,3)Gal xenoantigen expression as a gene therapy approach to cancer

Abstract: Galactose(␣1,3)galactose on the surface of cells of nonfor those cells expressing the antigen in a mixed cell popuprimate organs is the major xenoantigen responsible for lation. The mechanism of cell lysis mimicked that involved hyperacute rejection in xenotransplantation. The antigen is in hyperacute rejection: activation of the classical compsynthesised by (␣1,3)galactosyl transferase. Humans lack lement pathway by natural antibody specific for this enzyme and their serum contains high levels of pregalactose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…A similar selection of a-gal-positive tumor cells, after transfection with a retrovirus containing the a1,3GT gene, also requires the proliferation of the transfected cells for insertion of the gene into the genome of the cell, as previously demonstrated with human cell lines processed to express this epitope. [60][61][62][63] In contrast, transduction with AdaGT results in a-gal epitope expression in a large proportion of the tumor cells (Fig 2). Therefore, in vitro transduction with AdaGT is likely to be suitable for inducing expression of a-gal epitopes on freshly obtained tumor cells that are processed as autologous tumor vaccine.…”
Section: In Vivo Targeting Of Vaccinating Tumor Cells L Deriy Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…A similar selection of a-gal-positive tumor cells, after transfection with a retrovirus containing the a1,3GT gene, also requires the proliferation of the transfected cells for insertion of the gene into the genome of the cell, as previously demonstrated with human cell lines processed to express this epitope. [60][61][62][63] In contrast, transduction with AdaGT results in a-gal epitope expression in a large proportion of the tumor cells (Fig 2). Therefore, in vitro transduction with AdaGT is likely to be suitable for inducing expression of a-gal epitopes on freshly obtained tumor cells that are processed as autologous tumor vaccine.…”
Section: In Vivo Targeting Of Vaccinating Tumor Cells L Deriy Et Almentioning
confidence: 99%
“…50,[60][61][62][63] Freshly isolated tumor cells that are to be manipulated in a clinical setting to serve as an autologous tumor vaccine expressing a-gal epitopes, are mostly cells that are nondividing in vitro. Expression of these epitopes on nondividing tumor cells may be achieved by transduction with replication defective adenovirus containing the a1,3GT gene.…”
Section: Transduction Of Bl6 Cells By Adagtmentioning
confidence: 99%
“…Jager et al (27) showed that ␣-galexpressing human fibrosarcoma cells HT1080 became sensitive to CDC after the removal of CD55 and CD59 with nonhuman phosphatidylinositol-specific phospholipase C (PI-PLC). Hellrung et al (24) modified A549 to coexpress ␣-gal epitope peptides and PI-PLC.…”
Section: Discussionmentioning
confidence: 99%
“…The ␣1,3GT cDNA has been cloned from New World monkey (19), mouse (37), and bovines (29). It has been successfully expressed in a number of human cell lines (14,24,27,53). The ␣-gal epitope increases the sensitivity of tumor cells to human complementdependent cytolysis (CDC) in cell lines of human pancreatic cancer (1), hepatocellular carcinoma (66), and breast cancer (52).…”
mentioning
confidence: 99%
“…Based on the immunologic potential of anti‐αGal antibodies, the fundamental mechanisms of hyperacute rejection may be used to eradicate tumor whether tumoral cells express the αGal epitope or not. Retroviral‐mediated delivery of α1,3GT cDNA in human cells result in the membrane expression of αGal epitope, which provokes the complement‐dependent lysis of these cells [22–25]. It is also possible to increase the immunogenicity of autologous tumor vaccines in humans by expressing αGal epitope at the surface of tumoral cells [26–28].…”
Section: Introductionmentioning
confidence: 99%